Exploring the impact of a gratitude-focused meditation on body dissatisfaction: Can a brief auditory gratitude intervention protect young women against exposure to the thin ideal?. (June 2022) - Fraser, Erin; Misener, Kaylee; Libben, Maya
Abstract: This study aimed to determine if a brief gratitude-focused meditation would significantly impact body dissatisfaction, and whether it would serve as a protective factor from exposure to thin idealized images in a sample of undergraduate women. 176 participants ( M age = 19.75) engaged in either a gratitude meditation, mindfulness meditation, or listened to a recording of a history textbook. Women were subsequently exposed to a set of neutral images or thin ideal images. Women reported significant decreases in state body dissatisfaction following all auditory conditions, regardless of auditory content. Decreased levels of body dissatisfaction persisted through exposure to neutral images, but not through exposure to thin ideal images. Results indicated that both the gratitude and mindfulness interventions were effective in eliciting a significant increase in self-reported levels of gratitude and mindfulness compared to controls. The results of the study suggest that auditory micro-interventions can decrease body dissatisfaction in young adult women. However, further investigation into the optimal modality, length, and frequency of micro-interventions aimed at buffering the negative effects of idealized thin image exposure on women is needed. Highlights: Women listened to a brief audio recording (i.e., gratitude or mindfulness meditation, or a recording of a history textbook). All three interventions produced improvements in state body dissatisfaction from baseline to post-audio. Gratitude and mindfulness recordings were more effective than the history recording in enhancing mindfulness and gratitude. Positive effects from auditory micro-interventions did not fully buffer the negative effects of exposure to thin-ideal images.